2021
DOI: 10.3390/toxins13120877
|View full text |Cite
|
Sign up to set email alerts
|

Fish Cytolysins in All Their Complexity

Abstract: The majority of the effects observed upon envenomation by scorpaenoid fish species can be reproduced by the cytolysins present in their venoms. Fish cytolysins are multifunctional proteins that elicit lethal, cytolytic, cardiovascular, inflammatory, nociceptive, and neuromuscular activities, representing a novel class of protein toxins. These large proteins (MW 150–320 kDa) are composed by two different subunits, termed α and β, with about 700 amino acid residues each, being usually active in oligomeric form. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 69 publications
0
12
0
1
Order By: Relevance
“…Karatoxin 110kDa It is well known that fish venom is still largely unexplored as reported by (Silva et al, 2018;Xie et al, 2019;Gorman et al, 2020;Campos et al, 2021;Lopes-Ferreira et al, 2022) and in previous sections of this paper. Because there are few fish toxin sequences available as references, most of them are from Scorpaenidae and Synanceiidae families, it is challenging to research fish toxins and to create quick and effective techniques for wide exploration of toxin proteins or genes (Xie et al, 2017).…”
Section: Hypodytes Rubripinnis Nocitoxin 160kdamentioning
confidence: 65%
See 2 more Smart Citations
“…Karatoxin 110kDa It is well known that fish venom is still largely unexplored as reported by (Silva et al, 2018;Xie et al, 2019;Gorman et al, 2020;Campos et al, 2021;Lopes-Ferreira et al, 2022) and in previous sections of this paper. Because there are few fish toxin sequences available as references, most of them are from Scorpaenidae and Synanceiidae families, it is challenging to research fish toxins and to create quick and effective techniques for wide exploration of toxin proteins or genes (Xie et al, 2017).…”
Section: Hypodytes Rubripinnis Nocitoxin 160kdamentioning
confidence: 65%
“…Because there are few fish toxin sequences available as references, most of them are from Scorpaenidae and Synanceiidae families, it is challenging to research fish toxins and to create quick and effective techniques for wide exploration of toxin proteins or genes (Xie et al, 2017). Some recent studies have isolated and provided several toxins sequences using different techniques (Smith and Wheeler, 2006;Xie et al, 2016;Costa et al, 2018;Xie et al, 2019;Campos et al, 2021;Lopes-Ferreira et al, 2022), but due to a given number of venomous fish (>2000 species) (Saggiomo et al, 2021), it would be just a small portion of it.…”
Section: Hypodytes Rubripinnis Nocitoxin 160kdamentioning
confidence: 99%
See 1 more Smart Citation
“…Uz to, verukotoksin može lizirati membrane trombocita u krvi. 35 Kardiotoksičnost otrova manifestira se dvofaznim padom arterijskog tlaka u prvoj fazi, kasnijim dvofaznim porastom i naposljetku padom venskog tlaka. Smatra se da su promjene krvnog tlaka povezane s oslobađanjem endogenog acetilkolina iz muskarinskih receptora kao odgovora našeg organizma na otrov, iako to nije sasvim razjašnjeno.…”
Section: Toksini Ribaunclassified
“…The venom of snakes was approached in different aspects as the structural and functional variability in the composition of venoms from individual snakes [1], the mechanisms of action of whole venoms [2,3], the mechanisms of action of individual components as crotoxin [4], phospholipases A2 [5], metalloproteinases [6][7][8], and the oral immunity induced by whole venoms and their components [9]. Venoms from other animals are also reported; the venoms of centipedes [10], scorpions [11,12], fishes [13,14], and caterpillars [15], including microbial toxins [16]. The great potential for molecules derived from animal venoms as drug leads was also reviewed [17], and the antimicrobial [18], anticoagulant [19,20], and analgesic [21,22] effects have been highlighted in original studies reported here.…”
mentioning
confidence: 99%